Penerapan Bioteknologi Reproduksi Untuk Peningkatan Produktivitas Ternak Babi Di Sumatera Utara - Silalahi, Parsaoran (Jurnal Visi Eksakta, 2022)
The outbreak of the African Swine Fever (ASF) virus in North Sumatra Province has had a major impact on the economy of hundreds of thousands of pig farmer households. The remaining pig population after the outbreak of only about 15% has resulted in a price increase that has doubled from before and the pork is hard to find too. Most pig farmers switch to other livestock or other professions because many are traumatized by this ASF virus outbreak. To return to being the province that produces the most pork, several reproductive biotechnology can be implemented to accelerate the increase in the population of pigs and at the same time improve the genetic quality of pigs produced by the farmer. Some of the biotechnology referred to are estrus synchronization, superovulation, artificial insemination and frozen semen. Some of the above techniques should also be carried out in conjunction with the concept of upgrading pigs on a regular basis to get a good genetic composition for North Sumatra Province. There are several technical issues that can become obstacles in developing this reproductive biotechnology, but with good assistance it will produce reliable pig farmers who have efficient pigs so that they provide good profits for the breeders.